A Novel Mock Circuit to Test Full-Flow Extracorporeal Membrane Oxygenation - Stefan Caspari; Leonie S. Schwärzel; Anna M. Jungmann; Nicole Schmoll; Frederik Seiler; Ralf M. Muellenbach; Marcin Krawczyk; Quoc Thai Dinh; Robert Bals; Philipp M. Lepper; Albert J. Omlor (Membranes, 2022)
Extracorporeal membrane oxygenation (ECMO) has become an important therapeutic approach in the COVID-19 pandemic. The development and research in this field strongly relies on animal models; however, efforts are being made to find alternatives. In this work, we present a new mock circuit for ECMO that allows measurements of the oxygen transfer rate of a membrane lung at full ECMO blood flow. The mock utilizes a large reservoir of heparinized porcine blood to measure the oxygen transfer rate of the membrane lung in a single passage. The oxygen transfer rate is calculated from blood flow, hemoglobin value, venous saturation, and post-membrane arterial oxygen pressure. Before the next measuring sequence, the blood is regenerated to a venous condition with a sweep gas of nitrogen and carbon dioxide. The presented mock was applied to investigate the effect of a recirculation loop on the oxygen transfer rate of an ECMO setup. The recirculation loop caused a significant increase in post-membrane arterial oxygen pressure (paO2). The effect was strongest for the highest recirculation flow. This was attributed to a smaller boundary layer on gas fibers due to the increased blood velocity. However, the increase in paO2 did not translate to significant increases in the oxygen transfer rate because of the minor significance of physically dissolved oxygen for gas transfer. In conclusion, our results regarding a new ECMO mock setup demonstrate that recirculation loops can improve ECMO performance, but not enough to be clinically relevant.